Physiological and sanitary quality of soybean seeds cultivars under harvest delay - Fialho,Camila Andrade (2023)
Abstract The assessment of delayed harvesting of soybean seeds may help in the selection of cultivars more resistant to deterioration in the field. This work aimed to evaluate the physiological and sanitary quality of seeds of three soybean cultivars submitted to harvest delay. Seeds of the cultivars ‘NS 5959’, ‘BMX Potência’, and ‘TMG 1175’ were harvested in four periods (R8; R8 + 10 days; R8 + 20 days, and R8 + 30 days) and evaluated for the moisture content, germination, emergence, seedling growth, and fungal incidence. There was a reduction in germination and vigor of the seeds of the different soybean cultivars, especially when harvested at R8 + 20 and R8 + 30 days, due to deterioration in the field. In addition, the delay in harvest provided a higher incidence of fungi in the seeds, mainly Phomopsis sp., Aspergillus sp., and Cercospora kikuchii. In general, the cultivar ‘TMG 1175’ was more resistant to seed deterioration in the field caused by delayed harvesting.